A depth-integrated SPH model for debris floods: application to Lo Wai (Hong Kong) debris flood of August 2005. Issue 12 (14th February 2019) - Lin, Chuan; Pastor, Manuel; Yague, Angel; Tayyebi, Saeid Moussavi; Stickle, Miguel Martin; Manzanal, Diego; Li, Tongchun; Liu, Xiaoqing
Abstract : In this work an approach to representing debris floods and flows is proposed, based on a depth-integrated mathematical model and smooth particle hydrodynamics numerical technique. The main contributions of the present work are twofold: ( a ) an improved rheological Bingham model where solid fraction concentration can change as solids are entrained by the current and ( b ) implementation of boundary conditions describing the injection process of water from channel weirs into the domain. The model has been applied to the case of Lo Wai debris flood (Hong Kong, August 2005). Numerical results obtained with the proposed model are in reasonable agreement with field observation.